2023
DOI: 10.1186/s13098-023-01143-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between SGLT2 inhibitors and new-onset acute coronary syndrome in the elderly: a population-based longitudinal cohort study

Tsung-Kun Lin,
Mei-Chun Lee,
Yu-Han Cheng
et al.

Abstract: Background Several observational cohorts and meta-analytical studies on humans have shown that users of sodium-glucose cotransporter-2 inhibitors (SGLT2is) have a lower risk for new-onset acute coronary syndrome (ACS) than nonusers. However, some studies, including randomized clinical trials, reported the opposite results. This study aimed to investigate the impacts of a SGLT2i on new-onset ACS in a population. Methods We conducted a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…ref. [78] SGLT2-in use was associated with a non-significantly decreased risk of ACS. No difference in the SGLT2-in subtype was observed in subgroup analyses.…”
Section: T2d Patient Complexity and Endeavor Towards Precision Medicinementioning
confidence: 85%
See 1 more Smart Citation
“…ref. [78] SGLT2-in use was associated with a non-significantly decreased risk of ACS. No difference in the SGLT2-in subtype was observed in subgroup analyses.…”
Section: T2d Patient Complexity and Endeavor Towards Precision Medicinementioning
confidence: 85%
“…Although the common conclusion of the studies performed so far is that SGLT2-in and GLP-1ra improve CV outcomes in older (≥65) and frail patients, concerns remain when narrowly defined patient subgroups are used for the analysis such as older men and those older than 70 years [ 78 ]. In addition, frailty may change the harm–benefit balance of these drugs.…”
Section: T2d Patient Complexity and Endeavor Towards Precision Medicinementioning
confidence: 99%
“…To reduce the risks of cardiovascular diseases, current clinical guidelines highlight the importance of a multifactorial approach in diabetic management, including the use of anti-diabetic agents [2,3]. The current literature suggests that novel anti-diabetic medications such as sodium-glucose cotransporter-2 inhibitors (SGLT2I) and glucagon-like peptide receptor agonists (GLP1a) demonstrate promising protective effects against various major adverse cardiovascular events (MACE) and mortality [4][5][6]. Some studies suggested that the cardiovascular benefit of SGLT2I and GLP1a is enhanced when used in conjunction [7].…”
Section: Introductionmentioning
confidence: 99%